Reflection in the Context of the Epidemic: Does Death Anxiety Have a Positive Impact? The Role of Self-Improvement and Mental Resilience - Luo, Yang; Guo, Rui; Huang, Chaohua; Xiong, Yan; Zhou, Fei (Frontiers in Psychology, 2022)
Public health emergencies can trigger individual death anxiety. Most previous studies focus on the negative effects of death anxiety via the Western materialistic view, neglecting both the positive aspects of death anxiety within the Chinese cultural background and the positive effects of death anxiety upon environmental consumption. By implementing the unique Chinese cultural background for the concepts of justice and interests, this study explores the positive influence of individual death anxiety on altruistic environmental consumption during the COVID-19 crisis by analyzing personal life reviews and other sources. The results show that (1) under the guidance of the correct concept of justice and benefit, individuals with high death anxiety during the epidemic period not only enhance their self-esteem through positive self-perception and social evaluation, but they are more inclined to benefit from other environmental consumption behaviors and attain a symbolic self-survival; and (2) during the epidemic period, mental resilience, as a transformation mechanism of external defense and the internal growth of death psychology, can directly affect altruistic environmental consumption by consumers without relying on external standards. In the context of the Chinese culture’s concept of justice and interests, this study enriches the knowledge of fear management theory and the positive impact of death anxiety on environmental consumption. The introduction of mental resilience as a boundary condition has important theoretical and practical significance within the study of consumer behavior in public health emergencies and post-epidemic economic recovery